This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Super, that is exactly how it is supposed to be done
The n t h term is t n = n 2 − 1 0 n + 5 0 n 2 . So, t 1 0 − n = ( 1 0 − n ) 2 − 1 0 ( 1 0 − n ) + 5 0 ( 1 0 − n ) 2 = n 2 − 1 0 n + 5 0 ( 1 0 − n ) 2 . Therefore t n + t 1 0 − n = 2 for n = 1 0 − n or n = 5 and t 5 = 1 . Hence the required sum is 4 × 2 + 1 = 9 .
Super, that is exactly how it is supposed to be done
Problem Loading...
Note Loading...
Set Loading...
Similar solution as @Alak Bhattacharya 's
S = n = 1 ∑ 9 n 2 − 1 0 n + 5 0 n 2 = 2 1 n = 1 ∑ 9 ( n 2 − 1 0 n + 5 0 n 2 + ( 1 0 − n ) 2 − 1 0 ( 1 0 − n ) + 5 0 ( 1 0 − n ) 2 ) = 2 1 n = 1 ∑ 9 ( n 2 − 1 0 n + 5 0 n 2 + n 2 − 1 0 n + 5 0 n 2 − 2 0 n + 1 0 0 ) = 2 1 n = 1 ∑ 9 n 2 − 1 0 n + 5 0 2 n 2 − 2 0 n + 1 0 0 = 2 1 n = 1 ∑ 9 2 = n = 1 ∑ 9 1 = 9 By reflection k = a ∑ b f ( k ) = k = a ∑ b f ( a + b − k )